2020
DOI: 10.1111/manc.12323
|View full text |Cite
|
Sign up to set email alerts
|

Regime shifts in the effects of Japan’s unconventional monetary policies

Abstract: The use of unconventional monetary policies-that is, policies by central banks to pursue further monetary easing by unconventional instruments such as large-scale asset purchases once conventional policy rates have been lowered to virtually zero percent-has become a common practice among major central banks since the outbreak of the global financial crisis triggered by the collapse of Lehman Brothers in 2008. These unconventional measures continued even after the acute phase of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…However, banks seem to have supported profitability by increasing noninterest income through charging other fees. 1 The direct costs of negative reserves on bank reserves are also quantitatively small relative to banks' balance sheets. Central banks can further reduce these direct costs by charging negative rates only at the margin: for example, required bank reserves are typically exempt from negative interest rates and the Bank of Japan charges negative rates only on a subset of other bank reserves.…”
Section: Negative Interest Ratesmentioning
confidence: 99%
“…However, banks seem to have supported profitability by increasing noninterest income through charging other fees. 1 The direct costs of negative reserves on bank reserves are also quantitatively small relative to banks' balance sheets. Central banks can further reduce these direct costs by charging negative rates only at the margin: for example, required bank reserves are typically exempt from negative interest rates and the Bank of Japan charges negative rates only on a subset of other bank reserves.…”
Section: Negative Interest Ratesmentioning
confidence: 99%
“…Furthermore, the study found that the financial market impact of QQE policy is relatively large, indicating that QQE policy is more effective in influencing the financial market performance than the previous UMPs. Notably, using the vector autoregressive (VAR) model, the financial market impact of QQE policy remained supported in the subsequent studies by Otsubo (2018), Koeda (2019), Ryou et al (2019) and Miyao and Okimoto (2020).…”
Section: Unconventional Monetary Policiesmentioning
confidence: 99%
“…The finding has important policy implications as it can inform the Bank of Japan on which policy effectively influences the Japanese financial market conditions. JFEP 15,3 Empirical studies by Otsubo (2018), Koeda (2019), Ryou et al (2019) and Miyao and Okimoto (2020) found that the Bank of Japan's QQE policies have exerted a significant influence on the Japanese financial markets. However, the findings suffer from aggregation bias.…”
Section: Introductionmentioning
confidence: 99%
“…Kuo and Miyamoto (2016) find that QE increased employment, and the labor market has improved with unemployment falling steadily. Studies have also found that QE has stimulated economic output (Hausman and Wieland, 2014; Miyao and Okimoto, 2017).…”
Section: Unconventional Monetary Policy and The Bank Of Japanmentioning
confidence: 99%